SOCIOCULTURAL ASPECTS OF ETHNOGRAPHIC WORDS IN LITERARY-ARTISTIC TRANSLATION (on the materials of translation of the works of the poet-classic Ajiniyaz) - Rzaeva, R.K. (FAN va JAMIYAT, 2019)
The article deals with the study of ethnographic words as a means reflecting the culture of the people on the material of translation of the literary works of the famous Karakalpak poet-classic of the XIX-th century Ajiniyaz. Ethnographisms is a special layer in the vocabulary stock of the Karakalpak language and their investigation, especially in translation into English, is one of the actual issues. As an object for investigation we've chosen ethnographisms connected with traditions and customs of the Karakalpak people, connected with clothes, embelishments (jewelry) of the Karakalpak women and girls.